Drug Management On Availability Of Drugs In Pharmaceutical Installations Pabatu General Hospital Pt Pmn Using Fifo & Fefo Methods - Josua Pranata; Karmila Kaban; Maya Sari Mutia; Ulina Karo Karo (International Journal of Health and Pharmaceutical (IJHP), 2022)
The procurement of drugs is an important early stage in determining the success of the next stage because the planning stage is useful for adjusting the procurement needs with available funds to support health services in hospitals. The purpose of the study was to analyze the Management of Procurement of Insurance Medicines and Medicines for BPJS Health in the Pharmacy Unit of Bakti Timah Hospital, Pangkal Pinang, Bangka Belitung Islands Province in 2022. The research design used a qualitative descriptive method with a phenomenological approach, namely collecting, compiling, and analyzing so that a social phenomenon/fact can provide information. solving the problems encountered. This research was conducted at the Pharmacy Unit of Bakti Timah Hospital, Pangkal Pinang, Bangka Belitung Islands Province in April-May 2022. The sampling technique in this study used the Total Sampling technique, the number of samples was 5 pharmacists. The results of the research on the drug planning process at the Bakti Timah Pinang Hospital Pharmacy Installation, the drug budgeting process at the Bakti Timah Pinang Hospital Pharmacy Installation, the drug procurement process at the Bakti Timah Pinang Hospital Pharmacy Installation, the drug storage process at the Bakti Timah Pinang Hospital Pharmacy Installation, The process of storing drugs at the Pharmacy Installation of the Bakti Timah Pinang Hospital. Suggestions for hospital management to find out what strategies should be applied to increase revenue and services by reducing the percentage of prescriptions that are not served.